2002
DOI: 10.4037/ajcc2002.11.5.448
|View full text |Cite
|
Sign up to set email alerts
|

Acute Care Nurse Practitioners: Creating and Implementing a Model of Care for an Inpatient General Medical Service

Abstract: Changes in medical education and healthcare reimbursement are recent threats to most academic medical centers’ dual mission of patient care and education. Financial pressures stem from reduced insurance reimbursement, capitation, and changes in public funding for medical residency education. Pressures for innovation result from increasing numbers of patients, higher acuity of patients, an aging population of patients with complex problems, and restrictions on residency workloads. A framework for addressing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 14 publications
1
17
1
Order By: Relevance
“…The spectrum of activities performed by APPs in the VHA is similar to those reported in these inpatient medicine studies, although their scope of practice appears to be much broader than in these few small single academic center studies. 10,22,[29][30][31][32][33][34][35][36] For example, only 11% of hospitalist PAs did procedures in a 2006 Society of Hospital Medicine survey, whereas 50% did in our study. 36 Interestingly, we found that VHA NPs and PAs perform very similar tasks with similar caseloads despite differences in their background, training, regulation, reimbursement, and the longstanding observation that "nurse practitioners are not physician assistants."…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The spectrum of activities performed by APPs in the VHA is similar to those reported in these inpatient medicine studies, although their scope of practice appears to be much broader than in these few small single academic center studies. 10,22,[29][30][31][32][33][34][35][36] For example, only 11% of hospitalist PAs did procedures in a 2006 Society of Hospital Medicine survey, whereas 50% did in our study. 36 Interestingly, we found that VHA NPs and PAs perform very similar tasks with similar caseloads despite differences in their background, training, regulation, reimbursement, and the longstanding observation that "nurse practitioners are not physician assistants."…”
Section: Discussionmentioning
confidence: 87%
“…27,28 In spite of these concerns, we found widespread use of APPs with almost half of the VHA inpatient medicine services reporting use, which stands in contrast to prior research. 9,10,22,[29][30][31][32][33][34][35] APPs practice in a variety of acute and subacute inpatient medicine settings including academic, community, rural, and urban settings without many discernable differences. The spectrum of activities performed by APPs in the VHA is similar to those reported in these inpatient medicine studies, although their scope of practice appears to be much broader than in these few small single academic center studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 2 decades, the role of advanced practice providers (APPs), specifically nurse practitioners (NPs) and physician assistants (PAs), has expanded from primary care to inpatient settings. [1][2][3][4][5][6][7][8][9] The impetus for increasing the presence of APPs in hospitals is multifactorial and attributed to the need to build strong health systems that promote optimal patient outcomes in the face of workforce shortages and rising health care costs. 10 One major driver has been graduate medical education reform, which reduced the number of residents in subspecialty training programs, limited resident exposure to ICUs, and restricted total resident duty hours.…”
mentioning
confidence: 99%
“…[19][20][21][22][23][24] Historically, hospital-based APP service models have been implemented in medical and surgical subspecialty units and ambulatory clinics for which their scope of practice is limited to a narrow patient population. 1,6,9,25 Care delivery models in which APPs have been incorporated on a resident service or where the APP service works independently of residents have been studied on surgical trauma services. 7,26,27 By incorporating APPs, Christmas et al 27 demonstrated improved patient throughput and reduced length of stay (LOS) while decreasing resident service hours without affecting mortality or increasing the cost per patient.…”
mentioning
confidence: 99%